Detectability of minute temporal bone structures with ultra-high resolution CT - Hiraumi, Harukazu; Obara, Makiko; Yoshioka, Kunihiro; Ehara, Shigeru; Sato, Hiroaki (Auris, nasus, larynx, 2019)
Computed tomography (CT) is the imaging tool of choice in the diagnosis of temporal bone lesions. With the recent progress in imaging technology, CT with higher spatial resolution (Ultra-high resolution CT) has become available in the clinical setting. The purpose of this study is to evaluate the visibility of small temporal bone structures using ultra-high resolution CT. The visibility of 27 minute temporal bone structures on ultra-high resolution CT images was evaluated. Non-helical axial scans were performed in 18 normal hearing ears without previous otologic diseases. Visibility was scored by an experienced radiologist and otologist. Minute temporal bone structures including the ossicular chain, the crus of the stapes, the greater superficial petrosal nerve, and the anterior malleolar ligament were clearly visualized on ultra-high resolution CT. The stapedius muscle tendon and the chorda tympani exiting the posterior canaliculus and coursing medial to the malleus could be visualized. Ultra-high resolution CT provides good visualization of small temporal bone structures in normal subjects.